Deletion of histone demethylase Lsd1 (Kdm1a) during retinal development leads to defects in retinal function and structure - Ferdous, Salma; Shelton, Debresha A.; Getz, Tatiana E.; Chrenek, Micah A.; L’Hernault, Nancy; Sellers, Jana T.; Summers, Vivian R.; Iuvone, P. Michael; Boss, Jeremy M.; Boatright, Jeffrey H.; Nickerson, John M. (Frontiers in Cellular Neuroscience, 2023)
Purpose: The purpose of this study was to investigate the role of Lsd1 in murine retinal development. Lysine specific demethylase 1 (Lsd1) is a histone demethylase that can demethylate mono- and di-methyl groups on H3K4 and H3K9. Using Chx10-Cre and Rho-iCre75 driver lines, we generated novel transgenic mouse lines to delete Lsd1 in most retinal progenitor cells or specifically in rod photoreceptors. We hypothesize that Lsd1 deletion will cause global morphological and functional defects due to its importance in neuronal development. Methods: We tested the retinal function of young adult mice by electroretinogram (ERG) and assessed retinal morphology by in vivo imaging by fundus photography and SD-OCT. Afterwards, eyes were enucleated, fixed, and sectioned for subsequent hematoxylin & eosin (H&E) or immunofluorescence staining. Other eyes were plastic fixed and sectioned for electron microscopy. Results: In adult Chx10-Cre Lsd1fl/fl mice, we observed a marked reduction in a-, b-, and c-wave amplitudes in scotopic conditions compared to age-matched control mice. Photopic and flicker ERG waveforms were even more sharply reduced. Modest reductions in total retinal thickness and outer nuclear layer thickness were observed in SD-OCT and H&E images. Lastly, electron microscopy revealed significantly shorter inner and outer segments and immunofluorescence showed modest reductions in specific cell type populations. We did not observe any obvious functional or morphological defects in the adult Rho-iCre75 Lsd1fl/fl animals. Conclusions: Lsd1 is necessary for neuronal development in the retina. Adult Chx10-Cre Lsd1fl/fl mice show greatly impaired retinal function and morphology. These effects were fully manifested in young adults (P30), suggesting that Lsd1 affects early retinal development in mice.